Indonesian Stroke Management Neurointerventional Services Challenges - Fritz Sumantri Usman; Achmad Firdaus Sani; Fitri Octaviana; Merlin Prisilia Kastilong; Leny Kurnia; Theodorus K Hendartono; Andika S Atmadja; Yan Leo Tambunan; Syahrul Syahrul; Dodik Tugasworo Pramukarso (Journal of Neurointervention and Stroke, 2025)
Highlight: Stroke burden in Indonesia Challenges for Indonesian neurointerventionst ABSTRACT Introduction: Stroke is a leading cause of death and disability in Indonesia. Currently, stroke management has become more aggressive, and neurointerventionists are required to optimize acute stroke management. Objective: To determine the distribution of neurointerventionists in Indonesia and identify the obstacles faced in neurointervention services. Method: This cross-sectional study used an online questionnaire distributed to neurointerventionists in Indonesia between October and November 2024. Result: A total of 105 neurointerventionists completed the questionnaires. The distribution of neurointerventionists remains concentrated in Java, especially in Jakarta. The highest ratio of neurointerventionists to stroke cases was observed in Jakarta, while the lowest was in Lampung. West Java identified the largest gap in the number of neurointerventionists compared to Jakarta. Notably, 20.9% of neurointerventionists had not performed any neurointerventional procedures, and 46.8% reported challenges related to the funding of neurointerventional procedures through government insurance. Conclusion: Despite the increasing number of neurointerventionists in Indonesia, their distribution remains concentrated in Java. The main barrier was the funding of neurointerventional procedures through government insurance.